Evaluation of microstructure and fatigue properties of dissimilar AA7075/AA6061 joints produced by friction stir welding - Sarsilmaz, F.; Ozdemir, N.; Kirik, I. (Redakcia Kovove Materialy, 2012)
In this study, AISI 7075/AISI 6061 aluminum alloy plates were welded in butt position by friction stir welding (FSW). The welding process was performed using different process parameters, also investigating their effect on mechanical and fatigue behavior of FSW joints. The microstructural evolution of the material was analyzed by optical observations and SEM analysis of the weld cross sections. Tension tests were applied to welded parts to obtain the strength of the joints. Fatigue crack growth behavior and fatigue life of the welded joints have been evaluated by conducting the test using servo hydraulic controlled fatigue testing machine. According to the results, welding speed and tool profile in the tested range have major influence on the mechanical and fatigue properties of the FSW joints.
Keywords: fatigue lives; mechanical properties; friction stir welding